Front-line service managers' misbehaviour and disengagement: the elephant in the store?. Issue 5 (14th June 2019) - Hadjisolomou, Anastasios
Abstract : Purpose: The purpose of this paper is to revisit discussions on managerial work, seeking to re-examine the front-line service manager's position within the service triangle, and bring forward questions of agency that remain under-developed by scholars. Challenging the assumed unitarist and "consensus" standing point in organizations it recognizes that front-line managers, similarly to their subordinates, resist corporate demands and unveils stories of "battles" and disengagement towards their role, providing a rich empirical agenda regarding managerial misbehaviour. In order to explore front-line managers' agency issues, the paper adopts the framework of the dimensions of misbehaviour, as developed by Ackroyd and Thompson (1999), to capture and to better describe and understand the recalcitrant agential practices by front-line managers. Design/methodology/approach: The paper calls on qualitative data from two case study organizations in the Cyprus food-retail sector. In total, 46 interviews took place with participants across different departments and different management levels. This aimed for a better and deeper understanding of the research problem through understanding of the different perspectives. Findings: The evidence reveals the intensification of FLSMs' work and their feelings of pressure. FLSMs, however, did not stay apathetic and have utilized tactics to oppose the increasing workload and the expansion of their role. The paper classifies these tactics using the four dimensions of misbehaviour (Ackroyd and Thompson, 1999 ), namely, appropriation of time; work, product and identity. It shows that FLSMs not only resist corporate demands, like their subordinates, but also devised practices which are similar to workers. The data also reveal a variety in actions of misbehaviour between FLSMs depending on the level of customer interaction and their mobility on the shop floor. Research limitations/implications: Students of managerial work overlooked the political realities of management and the contested nature of (front-line service) management work. As this study has shown FLSMs across the shop floor strongly identify more with "front-line employees" than senior management, protecting their own interests within the employment relationship via oppositional actions and disengagement. FLSM is, of course, in an agency relationship with capital; however, this neglects the heterogeneity in interests at different levels of management. This paper shifts the focus of management research away from the traditional agency argument and discusses FLSMs as "misbehaving agents". It challenges the assumed unitarist and "consensus" standing point for FLSMs in organizations and calls HRM scholars to embrace a pluralist analysis in line management research. Practical implications: This research shows that FLSMs misbehave as an expression of discontent towards the expansion and intensification of their role. Yet, the data reveal variation in the organization of FLSMs' work across the shop floor and consequently variation in their actions of misbehaviour. This suggests that it is erroneous to presume a similar labour process for these managers and/or over-generalize their battling actions. HR practitioners will need to re-examine the roles of FLSMs in organizations, recognize the variety of interests within management, step away from rhetoric discourses of unproblematic devolvement of HR and managerial tasks to the front-line and appropriately review, redesign and re-organize front-line managerial work. Social implications: Although research has fruitfully located the powerlessness of front-line managers as a central theme in their analysis, the complexity of the front-line management position within the social relations of interactive service work and their "logic of action" within their labour process remains a relatively marginal theme in research. Indeed, FLSMs' position within the triangle, where managerial work is subject to degradation and trilateral conflicting dynamics and their battles within their own labour process, still remains under-explored. This study addresses this research lacuna focusing on the FLSMs' experiences on the front-end and their actions of misbehaviour within their labour process. Originality/value: The paper brings forward questions of agency that remain under-developed by scholars and unveils "stories of battles". It discusses FLSMs as "misbehaving agents" a question that is only superficially addressed in resistance and managerial studies. This paper challenges the embedded HRM unitarist assumption that FLSMs are conscientiously agents of the capital and reveals evidence suggesting the plurality of interests across management. HRM scholars, especially those discussed line managers as HRM partners, have overestimated FLSMs' identification with senior management and the strategic goals of the organization. As this study has shown FLSMs across the shop floor strongly identify with "front-line employees", protecting their own interests within the employment relationship via oppositional actions and disengagement.